2017
DOI: 10.3390/ijms18050954
|View full text |Cite
|
Sign up to set email alerts
|

Tubacin, an HDAC6 Selective Inhibitor, Reduces the Replication of the Japanese Encephalitis Virus via the Decrease of Viral RNA Synthesis

Abstract: Japanese encephalitis virus (JEV), a neurotropic flavivirus, annually causes over 30,000 Japanese Encephalitis (JE) cases in East and Southeast Asia. Histone deacetylases (HDACs) modulate lysine acetylation of histones and non-histone proteins, regulating many processes including inflammation and antiviral immune response. This study investigated antiviral activity of pan- and selective-HDAC inhibitors as host-targeting agents against JEV. Among HDAC inhibitors, selective HDAC6 inhibitors (tubastatin-A (TBSA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Thus, HSP90 inhibitors phenocopy JAK/STAT antagonism by flaviviruses, a similarity of function that we confirmed with side-by-side analyses. Our data revealed for the first time that flavivirus NS5 binds HSP90 to mediate broad STAT inhibition, which extends upon descriptive reports from other groups that identified JEV, DENV, and ZIKV NS5 interaction with HSP90, but did not define the relevance of this interaction [39][40][41]. Several DENV proteins have also been shown to bind HSP90 [37].…”
Section: Discussionsupporting
confidence: 53%
“…Thus, HSP90 inhibitors phenocopy JAK/STAT antagonism by flaviviruses, a similarity of function that we confirmed with side-by-side analyses. Our data revealed for the first time that flavivirus NS5 binds HSP90 to mediate broad STAT inhibition, which extends upon descriptive reports from other groups that identified JEV, DENV, and ZIKV NS5 interaction with HSP90, but did not define the relevance of this interaction [39][40][41]. Several DENV proteins have also been shown to bind HSP90 [37].…”
Section: Discussionsupporting
confidence: 53%
“…Histone proteins are key components of chromatin, acting as spools around which DNA winds, and play a significant role in gene regulation. Additionally, their function in viral infections is being increasingly acknowledged [ 51 , 52 , 53 , 54 ]. Currently, there are five major families of histones: H1/H5, H2A, H2B, H3, and H4.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that the polymerase of the Japanese encephalitis virus needs to be stabilized by Hsp90. The inhibition of HDAC6 leads to Hsp90 hyperacetylation, polymerase destabilization, and decreases viral replication [65]. Chaperones are involved in the MPyV life cycle, so their activity maintenance by HDAC6 may be important for viral propagation.…”
Section: Discussionmentioning
confidence: 99%